Calcineurin B-like domains in the large regulatory alpha/beta subunits of phosphorylase kinase. - Carrière, C; Mornon, J; Venien-Bryan, C; Boisset, N; Callebaut, I (2008)
Phosphorylase kinase (PhK) is a large hexadecameric complex that catalyzes the phosphorylation and activation of glycogen phosphorylase (GP). It consists in four copies each of a catalytic subunit (gamma) and three regulatory subunits (alpha beta delta). Delta corresponds to endogenous calmodulin, whereas little is known on the molecular architecture of the large alpha and beta subunits, which probably arose from gene duplication. Here, using sensitive methods of sequence analysis, we show that the C-terminal domain (named domain D) of these alpha and beta subunits can be significantly related to calcineurin B-like (CBL) proteins. CBL are members of the EF-hand family that are involved in the regulation of plant-specific kinases of the CIPK/PKS family, and relieve autoinhibition of their target kinases by binding to their regulatory region. The relationship highlighted here suggests that PhK alpha and/or beta domain D may be involved in a similar regulation mechanism, a hypothesis which is supported by the experimental observation of a direct interaction between domain D of PhKalpha and the regulatory region of the Gamma subunit. This finding, together the identification of significant similarities of domain D with the preceding domain C, may help to understand the molecular mechanism by which PhK alpha and/or beta domain D might regulate PhK activity.